The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11845-015-1327-0
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin: present and future

Abstract: Critically ill patients are frequently at risk of sepsis or inflammatory conditions. Procalcitonin (PCT) is a biomarker for critically ill patients to differentiate sepsis from non-infectious triggers of the systemic inflammatory response syndrome. It has been recently shown that PCT is a valuable tool to guide antibiotic treatment in patients with bacteria infections. However, PCT is also less than a universal and perfect biomarker, and its physiologic role remains unknown. An increase in PCT is associated no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 81 publications
(49 reference statements)
0
24
0
3
Order By: Relevance
“…PCT is an immunologically active protein induced through different steps of activation. Unlike various cytokines, PCT is activated in a time-dependent process, followed by adhesion and intercellular contact between injured cells and monocytes facilitated by adhesion molecule expression [14,15]. It is probable that increased PCT levels during DENV infection might be due to widespread inflammation in multiple organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCT is an immunologically active protein induced through different steps of activation. Unlike various cytokines, PCT is activated in a time-dependent process, followed by adhesion and intercellular contact between injured cells and monocytes facilitated by adhesion molecule expression [14,15]. It is probable that increased PCT levels during DENV infection might be due to widespread inflammation in multiple organs.…”
Section: Discussionmentioning
confidence: 99%
“…PCT is produced and released into the bloodstream in response to infection and/or inflammation in various tissues. In particular, hepatocytes and peripheral blood mononuclear cells are potent PCT secretors [15]. A recent systematic review and meta-analysis showed that PCT was a useful biomarker for the early diagnosis of sepsis in critically ill patients, with a sensitivity and specificity of 77% and 79%, respectively [16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these drawbacks, it is clear that serum PCT is associated with renal function in HBV-ACLF. Immunoneutralization of PCT will likely be a therapeutic approach for HBV-ACLF if the physiological effects can be clarified [24][25][26].…”
Section: Figurementioning
confidence: 99%
“…PCT is a 116-amino acid prohormone of calcitonin (CT) and is produced mainly by C-cells of the thyroid gland. It has a molecular weight of 13 kDa (Liu et al, 2015). In healthy state or in the absence of infections, PCT levels in the blood is very low (<0.1 ng/mL).…”
mentioning
confidence: 99%